Labor Supply, School Attendance, and Remittances from International Migration : The Case of El Salvador - Acosta, Pablo (Washington, DC, 2012)
The objective of this paper is to present microeconomic evidence on the economic effects of international remittances on households' spending decisions. Remittances can increase the household budget and reduce liquidity constraint problems, allowing more consumption and investment. In particular, remittances can afford investing in children's human capital, a key outcome for the discussion of the perspective of growth in a high recipient developing country. Robust estimates that take into account both selection and endogeneity problems in estimating an average impact of remittances are substantially different from least squares (OLS) estimates presented in previous studies, indicating the importance of dealing with these methodological concerns. After controlling for household wealth and using selection correction techniques such as propensity score matching as well as village and household networks as instruments for remittances receipts, average estimates suggest that girls and young boys (less than 14 years old) from recipient households seem to be more likely to be enrolled at school than those from nonrecipient households. Remittances are also negatively related to child labor and adult female labor supply, while adult male labor force participation remains unaffected on average. The results signaling that the additional income derived from migration increases girls' education and reduces women's labor supply, with no major impact on activity choice for males 14 years or older, suggest the presence of gender differences in the use of remittances across (and possibly, within) households.